2010
DOI: 10.1007/s10157-010-0298-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the aldosterone/mineralocorticoid receptor system in chronic kidney disease and metabolic syndrome

Abstract: Recent clinical and experimental studies have shown that aldosterone is a potent inducer of proteinuria and that mineralocorticoid receptor (MR) antagonists confer efficient antiproteinuric effects. We identified glomerular epithelial cells (podocytes) as novel targets of aldosterone; activation of MR injures podocytes possibly via oxidative stress, resulting in disruption of glomerular filtration barrier, proteinuria, and progression of chronic kidney disease. We also demonstrated that SHR/cp, a rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 91 publications
4
25
1
Order By: Relevance
“…33 We found that MR and CYP11B2 expression was enhanced in the peritoneum. CYP11B2 is a key factor in aldosterone synthesis.…”
Section: Discussionmentioning
confidence: 65%
“…33 We found that MR and CYP11B2 expression was enhanced in the peritoneum. CYP11B2 is a key factor in aldosterone synthesis.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the intra-adrenal RAS is highly sensitive to a variety of stressors, such as chronic salt overload and metabolic disorders. 33 In the clinical setting, paradoxical increase in aldosterone biosynthesis emerges in hypertensive or heart failure patients treated with AT 1 receptor antagonists or angiotensin-converting enzyme inhibitors. These observations suggest that there could also exist the RAS-independent stimulation of adrenal aldosterone production in some pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone levels increase in hypertension, DN, and chronic kidney disease [7][8][9] . In addition to its hemodynamic effects, the local effects of aldosterone on renal cells, including proximal tubular cells, mesangial cells, and podocytes, are currently being studied, and accumulating evidence suggests that aldosterone plays a pathogenic role in renal injury, leading to severe proteinuria and glomerular injury [10] .…”
Section: Introductionmentioning
confidence: 99%